Formulation of Ethanol Extract Lotion from Snake Fruit (Salacca zalacca) as an Antioxidant - Novandi Purba; Aminah; Intan (Jurnal FARMASIMED (JFM), 2026)
The skin is the outermost layer of the body that functions as the main protector from environmental exposure, including free radicals that can cause cell damage such as premature aging, dry skin, and various other skin disorders. Efforts to maintain healthy skin can be done through the use of appropriate cosmetic products, one of which is in the form of lotion. Lotion is a topical preparation that is easy to apply and can increase moisture and provide protection to the skin. Snake fruit (Salacca zalacca), a plant native to Indonesia that grows in tropical areas, is known to contain various bioactive compounds such as anthocyanins, flavonoids, flavonols, polyphenols, and β-carotene which have potential as antioxidants. This study aims to formulate and evaluate body lotion preparations based on ethanol extract of snake fruit (Salacca zalacca) as an antioxidant. The research methods include the preparation of simple drugs, extraction with ethanol solvents, body lotion formulations with varying extract concentrations (3%, 6%, and 9%), as well as physical quality evaluations including organoleptic tests, homogeneity, spreadability, pH, and irritation tests on volunteers. Antioxidant activity was tested using the DPPH (2,2- diphenyl-1-picrylhydrazyl) method. The results showed that all body lotion formulations met the physical evaluation requirements, with stable, homogeneous characteristics, good spreadability, and a pH that matched the skin's pH. The  irritation test showed that the preparation was safe to use because it did not cause irritation reactions on the volunteers' skin. Antioxidant activity testing showed that the ethanol extract of snake fruit had relatively strong antioxidant activity, with activity increasing along with increasing extract concentration in the preparation. Based on the results of the study, it can be concluded that the ethanol extract of snake fruit (Salacca zalacca) has the potential to be formulated into a stable, safe, and effective body lotion as an antioxidant to protect the skin from damage caused by free radicals.